Evaluation of Librarian Competency Improvement Training in Utilizing SLIMS 9 - Hartati, Puji; Saputra, Eka (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study aims to determine the application of each component of the CIPP evaluation, namely; (1) Context, (2) Input, (3) Process, and (4) Product on the results of training to increase librarian competency in using Slims 9 at SMA Negeri 1 Bengkulu Tengah. This study uses a qualitative using the context, input, process, product evaluation model. The data collection techniques used in this research are through interviews, observation and documentation studies. Data analysis techniques are carried out by condensing data, presenting data, and drawing conclusions. The results of the research show that the application of the context component is used to collect information regarding the needs that will be needed, the input component is used to collect information and input regarding how best to organize decisions and how to manage available resources, the process component is used to collect information on how to implement the training program, provide an overview of the smooth running of the program being implemented, as well as the application of product components used to collect information about the results of the training program being implemented.